Ductal Cell Reprogramming to Insulin-Producing Beta-Like Cells as a Potential Beta Cell Replacement Source for Chronic Pancreatitis - Jawahar, Aravinth P.; Narayanan, Siddharth; Loganathan, Gopalakrishnan; Pradeep, Jithu; Vitale, Gary C.; Jones, Christopher M.; Hughes, Michael G.; Williams, Stuart K.; Balamurugan, Appakalai N. (Current Stem Cell Research & Therapy, 2019)
Islet cell auto-transplantation is a novel strategy for maintaining blood glucose levels and improving the quality of life in patients with chronic pancreatitis (CP). Despite the many recent advances associated with this therapy, obtaining a good yield of islet infusate still remains a pressing challenge. Reprogramming technology, by making use of the pancreatic exocrine compartment, can open the possibility of generating novel insulin-producing cells. Several lineage-tracing studies present evidence that exocrine cells undergo dedifferentiation into a progenitor-like state from which they can be manipulated to form insulin-producing cells. This review will present an overview of recent reports that demonstrate the potential of utilizing pancreatic ductal cells (PDCs) for reprogramming into insulin- producing cells, focusing on the recent advances and the conflicting views. A large pool of ductal cells is released along with islets during the human islet isolation process, but these cells are separated from the pure islets during the purification process. By identifying and improving existing ductal cell culture methods and developing a better understanding of mechanisms by which these cells can be manipulated to form hormone-producing islet-like cells, PDCs could prove to be a strong clinical tool in providing an alternative beta cell source, thus helping CP patients maintain their long-term glucose levels.
Keywords: auto-transplantation